Exploited resources in the live bait trade on the Paraná coastal shore, southern Brazil - Rosa, Leonardo Cruz da; Guilherme, Pablo Damian Borges (Scientia Plena, 2014)
In this work were identified points of sale and the species commercialized as live baits for recreational fishery at Paraná coastal shore, southern Brazil. Five points of sale and six species, which two fish (Poecilia vivipara and Dormitator maculatus) and four crustaceans (Macrobrachium acanthurus, M. olfersii, Callichirus major and Litopenaeus schmitii) were recorded. Among them, only C. major and L. schmitii were previously evaluated regarding its use as live bait. In other hand, one of exploited species, D. maculatus, is on the Red List of Threatened Species of state of Paraná.